Using virtual reality to study pedestrian exit choice behaviour during evacuations. (May 2021) - Feng, Yan; Duives, Dorine C.; Hoogendoorn, Serge P.
Highlights: Pedestrian exit choice behaviour is investigated using VR and field experiment. The ecological validity of a particular VR simulator (smartphone-based HMD and 360° video) is established. Effect of different guidance information on exit choice behaviour is investigated using VR. Increasing visibility of exit sign has a significant influence on identifying exits. Other pedestrians and directional signs have significant influences on exit choice Abstract: Exit choice is vital to pedestrians' survival during evacuations. This paper presents the results of a VR experiment and a field experiment to study pedestrian exit choice behaviour during evacuations. Primarily, we compared pedestrian exit choice behaviour with a VR experiment and a field experiment to determine the ecological validity of a particular VR simulator (smartphone-based HMD and 360° video) as a research tool to study pedestrian exit choice behaviour. The results showed that the pedestrians' exit choice behaviour during the evacuation is similar in the field experiment and the VR experiment. Furthermore, we investigated whether and to what extent different types of information (i.e., exit signs, directional signs, presence of people) influence pedestrian exit choice during evacuations. The analysis focused on the commonalities and differences in the pedestrians' exit choice behaviour between the scenario without additional information and three scenarios with different types of information. The comparison between scenarios with different types of information illustrated that the presence of other pedestrians and directional signs have a significant influence on the participants' exit choice. Moreover, the results indicated that this VR simulator is applicable to study pedestrian exit choice behaviour during evacuations.